Serum Levels of Cytokines and IgE in Helminth-Infected Nigerian Pregnant Women and Children - Ganiyu Olatunbosun Arinola (Ubiquity Press, 2016)
Background: Helminth infection is an important health challenge. Because of modulation of the immune response toward T-helper 2 (Th2) cells, the immunologic interplay that manifest during the coexistence of helminth infection with other conditions is still poorly understood. Objective: This study determined the pattern of alteration in selected cytokines and immunoglobulin E(IgE) in pregnant women, preschool aged children, and school-aged children with helminth infection compared with uninfected groups. Methods: Seventeen pregnant women, 42 preschool-aged children, and 60 school-aged children with helminth infection (HI) were recruited into this study. They were matched with 21 pregnant women, 42 preschool-aged children, and 50 school-aged children without helminth infection (HN) who served as controls. Venous blood samples were collected from each participant and analyzed for serum levels of tumor necrosis factor α (TNF-α), interleukin-10 (IL-10), interleukin-8 (IL-8), interleukin-6 (IL-6), and IgE. Statistical analysis was done using the Student 't' test, and 'P' < .05 was considered as statistically significant. Findings: Only serum level of IgE was significantly elevated in HI pregnant women compared with HN pregnant women. In HI preschool- and school-aged children, serum levels of IL-8, IL-6, and IgE were significantly elevated compared with HN children. However, preschool- and school-aged children with HI had similar levels of serum TNF-α and IL-10 compared with their corresponding HN groups. Conclusions: It could be concluded that altered cytokines expression in children and pregnant women with helminth infection might have some implications on need for deworming programs to improve pregnancy outcomes and vaccine responses.